Nuclear servitude: subcontracting and health in the French civil nuclear industry - Thébaud-Mony, Annie (Amityville, 2009)
"France's nuclear facilities, which include 58 reactors, are half a century old. This is an industry in which risks to health in the short, medium, and long terms seem both the most dreaded and the most controversial. Every year, around 30,000 employees of "outside" companies perform maintenance in France's nuclear power plants. These workers receive 80% of the total annual occupational exposure to ionizing radiation in French nuclear plants. The sociological study presented in this book began with some workers' accounts of their experiences, and analyzes the social division of labor that divides workers' activities between highly specialized operations and "nuclear servitude" -a highly suggestive term designating the indispensable tasks that entail the most exposure to radiation while preparing for other maintenance operations.